Banana Leaf Culture Lifestyle And Wisdom Of Sisaket Tribe And Transferring Knowledge To Teenagers Sisaket Province, Thailand - et. al., Sahutsa Ponnil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Local wisdom is the cultural heritage of each social landscape that has accumulated goodness and virtue for a long time until the tribe has been in existence for a long time. Si Sa Ket Province, Thailand is considered one of the most multicultural areas such as Lao culture, Khmer culture, as well as Thai-Chinese culture that has passed into Thailand. Therefore, this research aimed (1) To study the knowledge, wisdom, and culture of the banana leaves of the Sisaket tribe. (1) To analyze the conditions factors of transferring the knowledge, wisdom, and culture of banana leaves. (3) To find ways to promote knowledge transfer, wisdom, and culture of banana leaves. And (4) to present information on promotion for the transfer of knowledge, wisdom, and culture of the Sisaket tribe's banana leaves to adolescents. This research was conducted in Sisaket Province. A sample of the quantitative research was 398 adolescents in Sisaket Province, who analyzed the data using descriptive statistics. The qualitative research contributors with in-depth interviews were 15 Sisaket tribal leaders, and 10 delegates using the Systematic Analysis method. The research results found that; (1) the knowledge, wisdom, and culture of the banana leaves of the Sisaket tribe consist of (a) traditions/rituals, (b) food, and (c) local materials. (2) the conditions factor of transferring the knowledge, wisdom, and culture of banana leaves were (a) Technology, (b) Motivation, (c) Traditions/Activities, (d) Natural Resources, and (e) Social. (3) The way to transfer knowledge, wisdom, and culture of the banana leaves of the Sisaket tribe is TRANS Model, including (a) T: Technology, (b) R: Rewards, (c) A: Activity, (d) N: Natural resource, (e5) S: Social, besides, the main approach that drives all approaches to achieve their goals is technology.